ISLAP: Advancing RFID System Security through an Improved Succinct and Lightweight Authentication Protocol - Khan, Salman; Iqbal, Zafar; Khan, Muhammad Ayaz; Sher, Burhan (International Bhurban Conference on Applied Sciences and Technology, 2023)
A radio frequency identification (RFID) system employs radio waves to communicate a unique pattern between a tag implanted in an RFID card and a reader to validate a user's identity and provide access. Because of its simplicity, it is regarded as a preferred authentication method. Along with extensive implementation, RFID's rapid growth raises several security challenges and threats. As a result, a secure authentication mechanism is required to address RFID security concerns. Among the different security techniques created by researchers, Succinct and Lightweight Authentication Protocol (SLAP) is a low-effort RFID architecture that can withstand security threats. According to our findings, previously published approaches are subject to stolen authenticator assaults, impersonation attacks, and anonymity issues. This research proposes an improved and efficient solution for RFID devices based on a lightweight authentication protocol known as ISLAP. This addresses the security issues and attacks observed in prior techniques. The proposed protocol is evaluated and validated using ProVerif, a software program designed to do reasoning about a protocol's security features. The proposed protocol was sufficiently safe, with optimal output compared to alternative solutions.